CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. (August 2017) - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M.; Watson, Gene E.; Bustamante, Mariona; Murcia, Mario; et al.
Abstract: Background: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p 450 3A (CYP3A) family as candidate MeHg susceptibility genes. Objectives: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. Methods: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n = 1160, 20 and 30 months of age, studied during the years 2001–2012), two subcohorts from Spain (INMA) (n = 625, 14 months of age, 2003–2009), and two subcohorts from Italy and Greece (PHIME) (n = 854, 18 months of age, 2006–2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 ( CYP3A7 ), rs776746 ( CYP3A5 ), and rs2740574 ( CYP3A4 ). Results: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]: = 2.9[1.53, 4.27] for CYP3A7 rs2257401 GG + GC, 2.51[1.04, 3.98] for CYP3A5 rs776746 AA + AG and 2.31[0.12, 4.50] for CYP3A4 rs2740574 GG + AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p < 0.05) in European cohorts only. Conclusions: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development. Highlights: Genetics may influence the neurotoxicity of MeHg The association between cord blood Hg and children's neurodevelopment was modified by variations in CYP3A5 and CYP3A7 CYP3A genes may influence the response to MeHg exposure during early life development